Uni- and crossmodal refractory period effects of event-related potentials provide insights into the development of multisensory processing - Johannsen, Jessika; Röder, Brigitte (Frontiers in Human Neuroscience, 2014)
To assess uni- and multisensory development in humans, uni- and crossmodal event-related potential (ERP) refractory period effects were investigated. Forty-one children from 4 to 12 years of age and 15 young adults performed a bimodal oddball task with frequent and rare visual and auditory stimuli presented with two different interstimulus intervals (ISI). Amplitudes of the visual and auditory ERPs were modulated as a function of the age of the participants, the modality of the preceding stimulus (same vs. different) and the preceding interstimulus interval (1000 or 2000 ms). While unimodal refractory period effects were observed in all age groups, crossmodal refractory period effects differed among age groups. Early crossmodal interactions (<150 ms) existing in the youngest age group (4-6 years) disappeared, while later crossmodal interactions (>150 ms) emerged with a parietal topography in older children and adults. Our results are compatible with the intersensory differentiation and the multisensory perceptual narrowing approach of multisensory development. Moreover, our data suggest that uni- and multisensory development run in parallel with unimodal development leading.